Effects of Fluency on Psychological Distance and Mental Construal (or Why New York Is a Large City, but New York Is a Civilized Jungle) - Alter, Adam L.; Oppenheimer, Daniel M. (Psychological Science, 2008)
People construe the world along a continuum from concretely (focusing on specific, local details) to abstractly (focusing on global essences). We show that people are more likely to interpret the world abstractly when they experience cognitive disfluency, or difficulty processing stimuli in the environment, than when they experience cognitive fluency. We observed this effect using three instantiations of fluency: visual perceptual fluency (Study 1b), conceptual priming fluency (Study 2b), and linguistic fluency (Study 3). Adopting the framework of construal theory, we suggest that one mechanism for this effect is perceivers' tendency to interpret disfluently processed stimuli as farther from their current position than fluently processed stimuli (Studies 1a and 2a).